Evaluation of nine maize inbred lines in diallel cross in relation to aluminum tolerance - Cançado, Geraldo Magela de Almeida (2002)
Nine maize inbred lines and their hybrid combinations were evaluated in incomplete diallel crosses to study the aluminum (Al) tolerance behavior. The phenotypic indexes used to determine Al tolerance were the relative seminal-root length (RSRL), the net seminal-root length (NSRL) and the hemathoxylin staining, determined after seven days of growth in nutrient solution with 222 mmoles L-1 of Al. The diallel crosses results showed that additive effects were more important than not additive effects, for all indexes evaluated. Maize lines L13, L724, L723, and L16 showed better behaviour for general combining ability (GCA) and specific combining ability (SCA) and are the more indicated for obtaining Al-tolerant hybrids. The correlation observed between NSRL and hematoxylin staining was 0.76, between NSRL and RSRL was 0.63 and between RSRL and hematoxylin staining equal to 0.27. Therefore, hematoxylin appears to be a suitable tool to assist Al-tolerance selection in maize breeding programs.